Syntax Element Partitioning for high-throughput HEVC CABAC decoding - Habermann, Philipp; Chi Ching Chi; Alvarez-Mesa, Mauricio; Juurlink, Ben (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2017)
Encoder and decoder implementations of the High Efficiency Video Coding (HEVC) standard have been subject to many optimization approaches since the release in 2013. However, the real-time decoding of high quality and ultra high resolution videos is still a very challenging task. Especially entropy decoding (CABAC) is most often the throughput bottleneck for very high bitrates. Syntax Element Partitioning (SEP) has been proposed for the H.264/AVC video compression standard to address this issue and the limitations of other parallelization techniques. Unfortunately, it has not been adopted in the latest video coding standard, although it allows to multiply the throughput in CABAC decoding. We propose an improved SEP scheme for HEVC CABAC decoding with eight syntax element partitions. Experimental results show throughput improvements up to 5.4× with negligible bitstream overhead, making SEP a useful technique to address the entropy decoding bottleneck in future video compression standards.